Toward a high-precision mass–energy test of the equivalence principle with atom interferometers - Zhou, Lin; Yan, Si-Tong; Ji, Yu-Hang; He, Chuan; Jiang, Jun-Jie; Hou, Zhuo; Xu, Run-Dong; Wang, Qi; Li, Zhi-Xin; Gao, Dong-Feng; Liu, Min; Ni, Wei-Tou; et al. (Frontiers in Physics, 2022)
The equivalence principle (EP) is a basic assumption of the general relativity. The quantum test of EP with atoms is an important way to examine the applicable scope of the current physical framework, so as to discover new physics. Recently we extended the traditional pure mass or energy tests of EP to joint test of mass-energy using atomic interferometer, and the violation parameter of mass is constrained to η0 = (−0.8 ± 1.4) × 10E−10 , and that of internal energy to ηE = (0.0 ± 0.4) × 10E−10 per reduced energy ratio. Here first we briefly outline the joint test idea and experimental results, then we analyze and discuss how to improve the test accuracy. Finally, we report the latest experimental progress towards higher precision mass-energy test of EP. We have observed atomic interference fringes of 2T = 2.6 s in the 10-m long-baseline atom interferometer. This free evolution time T to our best knowledge is the longest one realized in the laboratory, and the corresponding resolution of gravity measurement is 4.5 × 10E−11g per shot.